2019
DOI: 10.1017/cjn.2019.338
|View full text |Cite
|
Sign up to set email alerts
|

T2 Hypointensity Aids in the Diagnosis of Intracranial Metastatic Adenocarcinoma

Abstract: ABSTRACT:Background:The T2 hypointensity has been suggested to be associated with intracranial metastatic adenocarcinomas (IMA). The purpose of our study was to determine the association of T2 hypointensity with IMA.Methods:All patients with pathologically confirmed metastatic brain tumors who had a magnetic resonance imaging (MRI) at our institution in the last 10 years were retrospectively assessed. Qualitative assessment of the lesions on MRI was done by two separate readers who were blinded to the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…Studies have found T2 hypointensity in approximately 15% of metastases. 8 T2 hypointensity was observed in 20.9% of metastases in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Studies have found T2 hypointensity in approximately 15% of metastases. 8 T2 hypointensity was observed in 20.9% of metastases in our study.…”
Section: Discussionsupporting
confidence: 57%
“…10 Furthermore, a recently published study indicated that hypointense signal intensity within BM in conventional T2W sequence may aid in the diagnosis of adenocarcinoma histology. 24 However, assessment of BMs with conventional approaches may fail to reflect several characteristics of the tumor such as heterogeneity. Histogram analysis, by its ability to analyze lesions voxel by voxel, can establish the intensity distribution within a VOI and provide quantitative information on tumor characteristics such as symmetry, heterogeneity, and uniformity.…”
Section: Discussionmentioning
confidence: 99%
“…É aventada a possibilidade de o próprio tecido desses tumores ser a fonte do sinal. Porém, ainda não se sabe o motivo físico para este achado (20) .…”
Section: Miscelâneaunclassified